Peran FFPU Sebagai Norm Entrepreneur Agenda Women, Peace and Security (WPS) dalam RSK di Liberia - Johana Imanuella; Renitha Dwi Hapsari (Andalas Institute of International Studies, 2022)
Peacekeepers are front-line actors who are not only in direct contact with communities in post-conflict setting, but are also involved in the country’s security sector reform. This study is intended to find out how FFPU plays the role as WPS Agenda norm entrepreneur in SSR in Liberia. This study uses descriptive methodology using secondary data sources. The study shows that FFPU acted as a norm entrepreneur of the WPS agenda in SSR in Liberia through the unit’s involvement in Liberian police reform (Liberia National Police, LNP), which can be seen though the unit’s position as a role model for Liberian women, as well as given the responsibility to communicate the transformation of the police, from a corrupt institution to a trustworthy guardian.